PEMANFAATAN ALIRAN AIR IRIGASI SEBAGAI PEMUTAR TURBIN ULIR UNTUK PENGGERAK PEMBANGKIT LISTRIK - Suyanto, Muhammad; Subandi; Saputra, Alfin Dwi (Prosiding Seminar Nasional Teknoka, 2021)
Water flow is very necessary for residents in rural areas that are useful for irrigating rice fields but its use has not been maximized by the villagers, (PLTph) itself is a pico hydro power plant, said to be pico because it produces power from hundreds of Watts to 5 Kw which utilizes water as a prime mover. In this study the authors made a (PLTph) using a screwwheel and connected it to a DC generator as a voltage generator, this tool was designed to be placed on an irrigation channel which could later be used as alternative energy for village street lighting or so forth. In the design of this tool has a length of 2.5 meters with a width of 64 cm has two screw doors that are expected to accelerate rotation compared to one water entrance with a screw angle of 30 degrees which will later be connected to the multilevel pully to increase the rotation.In the testing of (PLTph) using a screwwheel obtained the highest results with a voltage of 13.1 Volt DC with the highest load current up to 0.80 while the generator amperes of 1.60 Amperes which can be used for loads up to 200 W at 200 Volt AC voltage at 80 Cm water level , and at the lowest voltage state produces 8.21 Volt DC with 0.15 Ampere load and 0.11 Ampere generator amperes that can be loaded with a 20 Watt lamp at 75 Cm water level.